Modernidade, racionalização e natureza: das brechas abertas pelo Protocolo de Quioto às soluções de mercado - Chyara Sales Pereira (2005)
Weber has outlined, in several works, that Modernity is characterized by six processes: the disenchantment and intellectualization of the world; the emergence of an ethos of impersonal and secular realization; the growing importance of technical knowledge, specialized in economy,administration and education; the objectification and depersonalization of right, economy and the political organization of the state; the progressive development of technically rational means to control man and nature; the tendency of dislocating the orientation from traditional to purelyinstrumental action. In spite of the different historical roots, these processes are connected by the fact that all of them favor the formal rather than the substantive rationally. In order to develop thisstudy we have assumed the postulate which affirms that the comprehension of a phenomenon is found in the meaning that the individuals attribute to their actions. Besides, we intend to a)understand how this process of ra to establish a new basis to the relation man versus nature; b) evaluate how actions which intend tomake possible the execution of the proposal of Sustainable Development taking the Kyoto Protocol as study case confronts the inversion of priorities established by the market, being it the only interactive space in which the actors can construe frameworks of understanding by means ofshared meanings.